Dopamine efflux in response to ultraviolet radiation in addicted sunbed users. (30th May 2016) - Aubert, Pamela M.; Seibyl, John P.; Price, Julianne L.; Harris, Thomas S.; Filbey, Francesca M.; Jacobe, Heidi; Devous, Michael D.; Adinoff, Bryon
Abstract: Compulsive tanning despite awareness of ultraviolet radiation (UVR) carcinogenicity may represent an "addictive" behavior. Many addictive disorders are associated with alterations in dopamine (D2/D3) receptor binding and dopamine reactivity in the brain's reward pathway. To determine if compulsive tanners exhibited neurobiologic responses similar to other addictive disorders, this study assessed basal striatal D2/D3 binding and UVR-induced striatal dopamine efflux in ten addicted and ten infrequent tanners. In a double-blind crossover trial, UVR or sham UVR was administered in separate sessions during brain imaging with single photon emission computerized tomography (SPECT). Basal D2/D3 receptor density and UVR-induced dopamine efflux in the caudate were assessed using 123 I-iodobenzamide ( 123 I-IBZM) binding potential non-displaceable (BPnd). Basal BPnd did not significantly differ between addicted and infrequent tanners. Whereas neither UVR nor sham UVR induced significant changes in bilateral caudate BPnd in either group, post-hoc analyses revealed left caudate BPnd significantly decreased (reflecting increased dopamine efflux) in the addicted tanners – but not the infrequent tanners – during the UVR session only. Bilateral ∆BPnd correlated with tanning severity only in the addicted tanners. These preliminary findings are consistent with a stronger neural rewarding response to UVR in addicted tanners, supporting a cutaneous-neural connection driving excessive sunbed use. Highlights: UVR induces striatal dopamine efflux in addicted, but not infrequent, sunbed users. UVR-induced dopamine efflux correlates with tanning addiction severity. A cutaneous-neural connection may drive excessive sunbed use.